The Development of an Integrated Interactive Digital Physics Module for the Larung Sesaji Culture of the Coastal Community of Jember Regency - Midroro, Jihan Ni'ami; Prastowo, Sri Handono Budi; Nuraini, Lailatul (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
The development of a digital physics module integrated with the offering culture of the coastal community of Jember Regency is based on the need for learning media that is able to link physics material with the phenomena that exist around students. The purposes of this media development are: (1) to describe the procedure for developing a digital physics module that is integrated with the local wisdom of the coastal community of Jember Regency, (2) to describe the validity of the module developed, (3) to describe the effectiveness of the module developed by the researcher. This research is a type of research and development (R&D) adapting Nieeven's development model. The digital module was developed with the help of Articulate Storyline 3 software. The respondents of this study were students of class X MIPA SMA Plus Al-Azhar Jember. The selection of islamic boarding school was aimed at preserving regional culture in the islamic boarding school environment and to ward off the views of modernists who think that islamic boarding school tend to be closed to use technology in the education. The Procedure for developing physics module consists of 3 stages, there are preliminary research, prototyping stage, and assessment stage until can produce learning media that integrate the culture of Larung Sesaji Coastal Community of Jember with class X physics lesson Newton’s Law of Gravity. The researchers module get an average validation score of 3.69. The digital physics module on a small-scale trial got an effectiveness score of 0.53 and on a large-scale trial it got a score of 0.71. Based on the research that has been done, the module developed by the researchers produces a product in the form of Newton Law’s of Gravity lesson integrated with the Culture of Larung Sesaji was classified as valid and effective to use to support the physics learning process in schools. The product of this research is a digital module which is a digital physics module that can be used via a laptop or computer that has chrome softwareKeywords: larung sesaji, local wisdom, Newton law’s, physics module.